Acellular dermal matrix seeded with autologous fibroblasts improves wound breaking strength in a rodent soft tissue damage model in neoadjuvant settings: $hEric Dominic Roessner, Steffen Thier and Peter Hohenberger, Markus Schwarz and Peter Pott, Dietmar Dinter, Mark Smith - Rößner, Eric; Thier, Steffen; Hohenberger, Peter; Schwarz, Markus; Pott, Peter Paul; Dinter, Dietmar; Smith, Mark (Journal of biomaterials applications, 2011)
Soft tissue defects following resectional surgery or trauma often result in deadspaces and require free or pedicled flaps. A programmed formation of filling tissue with enhanced biomechanical properties could be helpful. This study examined the effects on wound healing of acellular dermal matrix (ADM) seeded with autologous fibroblasts in a standardized rodent model. As pre- or postoperative radiotherapy is standard in many treatments of malignancies, we also investigated the effects of additional radiotherapy. Fischer rats were randomised and received a standardized unilateral soft tissue defect at the buttock. The defect was filled with ADM+fibroblasts or ADM alone. Controls received no filling. Either no radiation, adjuvant (postoperative) or neoadjuvant (preoperative) radiation was applied to the defect site. Six weeks later the defect volume was measured by MR-tomography. Wound breaking strength was examined by tensiometry according to German Industrial Standards. Filling of the defect side was significantly larger in ADM and ADM+fibroblast treated groups compared to the control group in all settings. Wound breaking strength in the unimodal setting was significantly improved in the ADM+fibroblasts group compared to the ADM group. In the neoadjuvant setting there was no significant difference between control and ADM group. However, the ADM+fibroblasts groups showed a significantly increased wound breaking strength compared to the control and the ADM-alone group. Seeded or unseeded ADM is able to fill deadspace in this rodent model in all settings. Implanting non-irradiated, vital, proliferating autologous fibroblasts on ADM results in significantly increased wound breaking strength.
Gesehen am 22.01.2020
First published december 30, 2009